ANALYSIS OF PUBLIC SERVICES IN URBAN CITY USING SERVQUAL DIMENSIONS - Putra, Dita Riyanto; Calderia, Joao Dos Reis (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. One of the apparent ways that government acts to address the fundamental needs of society is through public service. Research Purpose. This study aims to analyse the quality of public services using the SERVQUAL dimensions. Research Methods. This research uses a descriptive qualitative method in Blabak Village, Kediri City, based on the five dimensions of SERVQUAL. Data were collected through interviews, observations, and documentation, then analysed using interactive analysis with triangulation for data validity. Findings. Public services showed a fairly good quality. In terms of tangibles, facilities such as computers, printers, and internet networks are well available. However, limited space and seating are still obstacles in providing comfort for the community. In reliability, administrative services, especially the processing of population documents, run quite reliably, especially with the presence of the SAKTI application, which facilitates online processing and reduces queues. The responsiveness dimension pertains to officers’ readiness to serve and respond to community needs, despite technical constraints like internet connectivity. In the assurance dimension, people feel safe because the officers show a friendly and professional attitude, in accordance with the motto ‘Salam, Sapa, Senyum,’ which creates a warm and pleasant service atmosphere. Meanwhile, empathy can be seen from the officers' concern for the community, despite the limited number of personnel and diverse educational backgrounds, they still try to serve optimally. Conclusion. Public services have run quite optimally. However, improvements are needed in terms of infrastructure and the number of officers so that services can be more comfortable, fast, and efficient.